ANALISIS PROFIL SEKOLAH DASAR ISLAM TERPADU - Nurul Afifa; Sudjarwo Sudjarwo; Supomo Kandar (Program Studi Magister Manajemen Pendidikan)
The focuses of this study were on the aspects of the human resource management (teachers and students), the management of teaching and learning, the curriculum management, and the management aspects of the school committee involvement. Through qualitative approach (case study design), researcher collected data by interviewing, school documents and observing directly to the school. The collected data were analyzed in accordance with the management aspects of the focuses have been set to determine the causes. Furthermore, the data were compared for compliance with management theories in education. Integrated curriculum of the school can improve students' knowledge of religion, and active involvement of the school committee to assist the implementation of quality learning.Satu fokus dari penelitian ini adalah pada aspek manajemen sumber daya manusia (guru dan siswa), pengelolaan pembelajaran, pengelolaan kurikulum, dan aspek manajemen keterlibatan komite sekolah. Melalui pendekatan kualitatif (rancangan studi kasus), peneliti mengumpulkan data dengan wawancara, dokumen sekolah dan mengamati langsung ke sekolah. Data yang terkumpul dianalisis sesuai dengan aspek manajemen satu fokus telah ditetapkan untuk menentukan penyebab. Selain itu, data dibandingkan untuk mematuhi teori manajemen dalam pendidikan. Kurikulum Terpadu sekolah dapat meningkatkan pengetahuan siswa tentang agama, dan keterlibatan aktif dari komite sekolah untuk membantu pelaksanaan pembelajaran yang berkualitas.Kata kunci: manajemen sumber daya manusia, manajemen kurikulum, manajemen pembelajaran.